Analysis Concept Mastery of Students of class XII MIPA 1 SMA Negeri 11 Makassar on Colligative Properties of Solution Subject Using Two Tier Diagnostic Tests - Fitrah, Aulia Nurul; Yunus, Muh.; Husain, Halimah (ChemEdu, 2025)
This research aims to find out the percentage of students' concept mastery in class XII MIPA 1 SMA Negeri 11 Makassar on colligative properties of solutions subject. The subjects in this study were students of class XII MIPA 1 which consisted of 30 students. The instrument used is a Two-Tier Diagnostic Test with 20 items that have been validated by expert with a very high reliability value of Cronbach’s alpha on 0.877. The two-tier diagnostic test had 2 levels of questions. The first level is a choice of answers to questions, and the second level is a reason that refers to the answers in the first level. The test used to identify concepts mastery of students by analysed the pattern of answers given. Based on the results of the research, it was found that the percentage of students who understood the concept of the colligative property of solution was 42% where the percentage of the concept of explaining the colligative properties of the solution was 73.35%, calculating the concentration of 65%, measuring the decrease in vapor pressure of the solution 48.87%, measuring the increase in the boiling point of the solution 20, 78%, measuring the osmotic pressure of a solution of 36.65%, and analysing the phenomenon of colligative properties of solutions in daily life of 31.65%. The percentage of concept mastery based on concept mastery indicators at the remembering stage (C1) 76.7%, understanding stage (C2) 66.67%, applying stage (C3) 57.23%, analysing stage (C4) 43.98%, evaluating stage (C5) 12.47%, and stage of creating (C6) 8.32%.